Product-market strategy and underwriting performance in the United Kingdom's property–casualty insurance market. Issue 11 (24th July 2019) - Adams, Mike; Upreti, Vineet; Chen, Jing
ABSTRACT: Drawing on a framework from the organizational economics literature, we utilize a panel data design to examine empirically the effect of motor insurance and liability insurance business on the overall underwriting performance of insurers operating in the United Kingdom's (UK) property–casualty insurance market. We find that participation in liability insurance contributes positively to underwriting performance, whereas motor insurance is associated with inferior underwriting performance. Additionally, we find that higher reinsurance ratio is associated with better underwriting performance, but reduced profit margins. Our results show that higher leverage too is associated with better underwriting performance. We conclude that our results could have potentially important commercial and/or policy implications.